Performances of phosphate-solubilizing microorganisms on soil chemical properties under different soil characteristics: a meta-analysis - Bachtiar, Taufiq; Syahputra, Akhmad Rasyid; Citraresmini, Ania; Nurjayati, Ratih; Hidawati, Hidawati; Rachmawati, Veny; Mulyono, Asep (Journal of Degraded and Mining Lands Management, 2024)
The addition of phosphate-solubilizing microorganisms (PSM) as biofertilizers can improve the quality of soil properties. A meta-analysis study was conducted to analyze the effect of PSM on soil properties. This meta-analysis has analyzed 20 research articles published between 1990 and 2023, which have reported the influence of PSM on soil properties. The value of effect size (ES) Hedges'd of available-P is 3.047 (p<0.001), ES of available K is 2.102 (p<0.001), ES of soil nitrogen (N) is 1.706 (p<0.001), ES of pH is  -2.738 (p<0.001), ES of soil organic carbon (SOC) is 1.087 (p=0.004), ES of N-NH4 is 0.636 (p= 0.013), ES of N-NO3 is 2.643 (p< 0.001), ES of phosphatase is 5.001 (p< 0.001), ES of alkaline phosphatase is 22.956 (p<0.001), and ES of acid phosphatase is 23.104 (p<0.001). The results showed that in terms of phosphate solubility, PSM is more effective on alkaline soils with high SOC content, very high P availability, and a sandy loam texture. PSM is more effective for K solubility on acidic soils, with very high SOC content, high P availability, and a loamy texture. PSM is effective in increasing soil N with acid soil characteristics, low SOC content, moderate available P content, and clay texture. According to this study, the Penicillium fungus ranks second in the fungal group in terms of phosphate solubilization capacity after the genus Azotobacter. The genus Peronospora showed the greatest potential in increasing soil N. In contrast, Burkholderia showed the greatest effectiveness in solubilizing K.